Prevalence and factors affecting early initiation of breastfeeding in rural areas of Dibrugarh district, Assam - Borah, Monmohan; Baruah, Jenita; Baruah, Rupali; Boruah, Manjit (International Journal Of Community Medicine And Public Health, 2019)
Background: Early or timely initiation of breastfeeding, specifically within 1 hour of birth has benefits for survival and beyond and it is recommended by the World Health Organization. Breastfeeding initiation after the first hour of birth doubles the risk of neonatal mortality. The present study has been conducted to estimate the prevalence and determine the factors affecting early initiation of breastfeeding in rural areas of Dibrugarh, district, Assam. Methods: Community based cross sectional study from May 2017 to April 2018 among mothers having children in the age group 0 to 23 months in the rural areas of Dibrugarh district. The sample size calculated for the study was 360 children. Results: The results were analyzed for 334 children. Prevalence of early initiation of breastfeeding was found to be 54.8%. On multivariate regression analysis the occupation and education of mothers, number of antenatal checkup visits, type of delivery and religion were found to be independently associated with early initiation of breastfeeding. Conclusions: This study reveals that the early initiation of breast feeding is lower in rural areas of Dibrugarh district. The findings clearly highlight the importance of imparting health education to family members and mothers right from antenatal period on infant and child feeding practices.